The Role of Adolescent Posyandu in The Detection And Prevention of Anemia: A Health Belief Model Approach - Erlin Kiriwenno; Irma Ika Sari; Nurhayati Kasim; Arindiah Puspo Windari; Runi Anggriani La Amin (Jurnal Ners, 2026)
Anemia remains a serious public health problem, particularly in low- and middle-income countries. This condition occurs when the number of red blood cells or hemoglobin levels falls below normal limits. Data from the Central Maluku District Health Office indicate that the prevalence of anemia is higher among adolescent girls than among adolescent boys. This study aims to examine the role of adolescent Posyandu (community- based health posts) in the detection and prevention of anemia using the Health Belief Model approach. This study employed a qualitative research method with a phenomenological approach. Informants were selected using purposive sampling. Participants consisted of four adolescent girls aged 10–19 years, one youth health cadre, two health workers, and one village government representative. Data collection techniques included interviews, documentation, and observation. The results showed that anemia-related problems in Central Maluku District were influenced by several factors, including: 1) perceived susceptibility to anemia (knowledge of anemia and its causes), 2) perceived severity (risks and impacts of anemia), 3) perceived benefits (consumption of iron supplementation tablets and participation in adolescent Posyandu), 4) barriers to prevention (low adolescent participation and low adherence to iron supplementation tablet consumption), and 5) the role of adolescent Posyandu (health education/counseling and health examination services). The study concludes that adolescent Posyandu plays an important role in preventing anemia among adolescents. Through education, distribution of iron supplementation tablets, and hemoglobin testing, adolescent Posyandu serves as the frontline in promotive and preventive efforts to address adolescent anemia.